Back to the Roots of Nursing: Qualitative Study on the Experience of Nurses in the Front Line During the COVID-19 Pandemic - De Benedictis, Anna; Gualandi, Raffaella; Saccoccia, Sabrina; Pensieri, Claudio; Piredda, Michela; De Micco, Francesco; Marchetti, Anna; Facchinetti, Gabriella; Pasquarelli, Alessia Assunta; De Carolis, Chiara; Di Blasio, Irene; Tartaglini, Daniela; et al. (Frontiers in Medicine, 2022)
The COVID-19 emergency has led many health facilities to reorganize themselves in a very short time to meet the urgent needs for intensive, semi-intensive or ordinary care of SARS-CoV-2 patients. In this pandemic, characterized by speed of transmission and severity of respiratory symptoms, care has been affected by the increase in volume and clinical complexity of patients, the sudden and unpredictable staff decrease and the lack of support from family members / caregivers. At the same time, experience in the field has shown how 'informal' resources have been activated, which enabled to treat the highest possible number of patients above the real availability of resources. The purpose of this study was to explore the experiences of nurses involved in frontline care (COVID Centers) during the pandemic with a particular focus on professional motivation and on the development of technical-professional and personal skills. A study with a qualitative research design using focus group technique was conducted. Two focus groups were held with 9 nurses. Data were analyzed with inductive content analysis. The findings can be summarized in five main categories: professional identity; motivation and sense of mission; development of professional and personal skills; spirituality; person-centered care; uniqueness of the lived experience. These findings shed new light on the correlation between motivation, professional identity and value, sense of duty and sense of belonging to the professional group. Moreover, the experience in the COVID Centers represented a valuable opportunity for participants to rediscover some specific issues related to nursing professional identity and to develop new personal and technical-professional skills in a very short time. Finally, nurses experienced once again how the nurse-patient relationship and basic care are essential to provide effective and excellent care, even and especially for patients in critical conditions. Nurses re-discovered, in a careful body care and basic care, irreplaceable elements to give back to patients, often dying, their own dignity, and all the needed closeness and attention necessary also to compensate the absence of the loved ones. These elements represent a way to concretely and deeply express the ethics of a job well done in nursing.